ANALISIS PERENCANAAN PLTS SEBAGAI SUPPLY ENERGI LISTRIK CHARGE STATION DI BRANDA CAFE UNIVERSITAS PEMBANGUNAN PANCA BUDI - Muhammad Farijal; Pristisal Wibowo; Dino Erivianto (CV. Hawari, 2026)
availability of sustainable electrical energy is an essential requirement in the campus environment, particularly to support academic activities of students and academic staff in the use of electronic devices such as mobile phones and laptops. Currently, charge station facilities generally rely on conventional electrical energy supplied by the national grid, which has limitations and causes environmental impacts. Therefore, the utilization of renewable energy is an alternative solution that needs to be developed. This study aims to analyze the planning of a Solar Power Plant (Photovoltaic System) as a source of electrical energy for charge stations at Branda Cafe, Universitas Pembangunan Panca Budi. The research method employed is a quantitative descriptive approach, which includes analysis of daily electrical energy demand, charge station design planning, calculation of the number and capacity of solar panels, battery capacity planning, and selection of supporting PLTS components such as solar charge controllers and inverters. The results show that the total daily electrical energy demand of the charge station is 3,600 Wh. To meet this demand, the PLTS system is designed using nine 100 Wp solar panels, three 12 V 100 Ah batteries, one MPPT-type solar charge controller, and a 5,000 W inverter. The designed PLTS system is capable of providing a reliable, independent, and environmentally friendly electricity supply. Thus, the implementation of PLTS-based charge stations on campus can serve as an alternative solution to support sustainable renewable energy.